Comparison of different techniques of cataract surgery in bacterial contamination of the anterior chamber in diabetic and non-diabetic population - M Ashok Kumar; Sheen S Kurien; Stephen Selvaraj; Uma Devi; S Selvasundari (Indian Journal of Ophthalmology, 2012)
Aim : To compare the bacterial contamination of the anterior chamber (AC) between manual small incision cataract surgery (SICS) and phacoemulsification (Phaco). To study the conjunctival flora and bacterial contamination of AC between well-controlled diabetics and non-diabetics. Materials and Methods : Three hundred and sixty-eight patients were randomized to manual SICS and Phaco. Sixty-eight patients were excluded for not completing follow-up or for intraoperative complications like posterior capsule rupture. One hundred and fifty patients in each group were finally analyzed. Conjunctival swabs were taken on admission, after one day of topical ofloxacin and 15 min after 5% Povidone Iodine (PI) instillation. AC aspirate at the end of the surgery was also cultured. Results : Fifty-six (18.66%) patients had positive conjunctival swab on admission which was reduced to 19 (6.33%) with topical ofloxacin and to five (1.66%) with instillation of 5% PI. AC contamination in both manual SICS and Phaco was 0.66%. The conjunctival flora in diabetics was similar to non-diabetics. None of the diabetics had AC contamination. Statistical analysis was performed by Chi-Square test (with Yates′ correction). Conclusion : Statistically significant reduction in conjunctival flora was achieved with topical ofloxacin and 5% PI instillation and AC contamination in both manual SICS and Phaco was minimal (0.66%). Well-controlled diabetics who underwent cataract surgery in this study had similar conjunctival flora and AC contamination as non-diabetics.